POEMS syndrome presenting as presumed chronic glomerulonephritis with a 1-year delay in diagnosis: a case report - Li Liu; Mingpeng Li; Fugang Li (Frontiers in Medicine, 2026)
Background Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal protein, Skin changes (POEMS) syndrome is a rare paraneoplastic disorder driven by an underlying plasma cell dyscrasia. While renal involvement is common, it typically manifests after neurological or dermatological symptoms. Chronic glomerulonephritis-like manifestations as the sole initial feature for a prolonged period are exceptionally rare and can lead to delayed diagnosis. Case presentation A 38-year-old woman presented with a 1-year history of foamy urine and a 1-week history of lower limb muscle pain. She had previously been treated with irbesartan for presumed chronic glomerulonephritis. Two months prior to admission, she developed lower limb numbness, followed by progressive muscle pain. Physical examination revealed cervical lymphadenopathy and left-sided cardiomegaly. Laboratory investigations demonstrated proteinuria, mild renal impairment, and a serum monoclonal immunoglobulin A (IgA)- λ protein on immunofixation electrophoresis. Nerve conduction studies confirmed severe demyelinating polyneuropathy. Imaging revealed pericardial effusion, splenomegaly, and bilateral renal enlargement. Following multidisciplinary consultation, subsequent investigations revealed markedly elevated serum vascular endothelial growth factor (VEGF) and patchy, slightly high-density shadows in bilateral iliac bones on abdominal computed tomography (CT), which supported the definitive diagnosis of POEMS syndrome. At follow-up, the patient was initiated on lenalidomide and dexamethasone therapy and is currently undergoing autologous stem cell transplantation at a tertiary care center, showing significant symptomatic improvement. Conclusion In patients with an unexplained chronic glomerulonephritis-like presentation that is refractory to standard therapy, POEMS syndrome should be considered in the differential diagnosis, even in the absence of typical skin or bone changes. Early serum immunofixation and VEGF assessment are critical for avoiding a delayed diagnosis.